Nutrient value of wild fodder species and the implications for improving the diet of mithun (Bos frontalis) in Dulongjiang area, Yunnan Province, China - Geng, Y.; Ranjitkar, S.; Yan, Q.; He, Z.; Su, B.; Gao, S.; Niu, J.; Bu, D.P.; Xu, J.C. (Elsevier, 2020)
Wild fodder plants are valuable because they provide an important livestock feed resource globally, especially for smallholder farmers, and have important roles in natural resource management. In-depth knowledge of wild forage plants can motivate local people for feed resource and habitat conservation of threatened herbivores such as Mithun (Bos frontalis). Mithun occur in small patches in the mountains of Dulongjiang, nearby villagers domesticated this animal but left animal to freely graze in the mountains. Many fodder plants occur in these mountains, however, little is known about their nutritional value. We conducted an ethnobotanical survey to document important wild fodder plants consumed by mithun in the Dulongjiang Township. The nutritional content of 21 highly mentioned wild fodder plants in an ethnobotanical survey was examined. Laboratory analysis showed that Fagopyrum dibotrys were the fodder species with the highest crude protein (CP) content (26.89%), followed by Polygonum molle (21.88%) and Hydrangea longipes (21.12%). Synthesis of relative feed value index and grey relational grade, P. molle, H. longipes and Tetrastigma obtectum were ranked the top three nutritional fodders. There was a significant difference between 21 species on their in vitro digestibility and the most highly digestible fodder species was Elatostema hookerianum. Linear model analysis on relationship between frequency of citation of 21 wild forage plants by local farmers and their nutrient composition showed that the frequency was significantly positively correlated with the nutritional value of the feed (R2 = 0.28, P < 0.05). We concluded that these species have high nutritional values to improve mithun production in integrated crop-livestock systems. Fodder species or mixtures of species with useful nutritional characters could be cultivated to improve livestock productivity, habitat conservation including that of mithun and wild forage resource management.